Immunohistochemistry in the classification of systemic forms of amyloidosis: a systematic investigation of 117 patients - Schönland, Stefan; Hegenbart, Ute; Bochtler, Tilmann; Mangatter, Anja; Hansberg-Otte, Marion; Ho, Anthony Dick (Blood, 2012)
Amyloidoses are characterized by organ deposition of misfolded proteins. This study evaluated immunohistochemistry as a diagnostic tool for the differentiation of amyloid subentities, which is warranted for accurate treatment. A total of 117 patients were systematically investigated by clinical examination, laboratory tests, genotyping, and immunohistochemistry on biopsy specimens. Immunohistochemistry enabled the classification in 94% of the cases. For subsequent analysis, the patient population was divided into 2 groups. The first group included all patients whose diagnosis could be verified by typical clinical signs or an inherited amyloidogenic mutation. In this group, immunohistochemical subtyping was successful in 49 of 51 cases and proved accurate in each of the 49 cases, corresponding to a sensitivity of 96% and a specificity of 100%. The second group included patients with systemic light chain amyloidosis without typical signs, senile transthyretin, or hereditary amyloidosis with a concomitant monoclonal gammopathy. Immunohistochemistry allowed to define the subentities in 61 of 66 (92%) of these cases. Immunohistochemistry performed by a highly specialized pathologist combined with clinical examination and genotyping leads to a high accuracy of amyloidosis classification and is the standard in our center. However, new techniques, such as mass spectroscopy-based proteomics, were recently developed to classify inconclusive cases.